Financial Protection of Old Age in The Opinion of Different Generations of Respondents - Maria PLONKA; Jolanta STANIENDA (Communications of International Proceedings, 2021)
The demographic changes (aging of the population) taking place in developed countries for about 50 years are the source of new challenges in the economic, social, and cultural area. The predicted increasing burden on the public sector on expenses for securing people in retirement age and the ever-lower replacement rate imply the necessity of a scientific discussion on the individual caution of citizens related to securing their own old age. The basic questions and goals posed in the study were formulated as follows: is the intergenerational awareness of old age security changing and how? The subject of the own research was to find out the opinions of respondents in four age cohorts from 18 to 90+ on the limits of old age, differences between the stereotype of old age and their own perception of old age, and to examine preferences regarding the financial security of their own old age. The research was carried out in 2021 in Poland using a questionnaire using the technique CAWI (N= 181) i PAPI (N= 62). The results of the survey allow for the conclusion that, in the opinion of the respondents, the age limit moves with age, the stereotype of old age created by the media is negative, but the image of one's own old age is more optimistic than the stereotype, and there are intergenerational differences in the approach to financial security of old age. This implies the need to build public awareness on this subject.
Keywords: Old Age Security; Retirement Pension; Individual Retirement Plan; Attitudes; Retirement Awareness.